EFEKTIFITAS ACTIVE ASSISTIVE RANGE OF MOTION TERHADAP PENURUNAN KGD PADA PASIEN DIABETES MELLITUS TIPE II - Hati, Yulis; Muchsin, Rosanti; Lestari, Ayu (Universitas Prima Indonesia, 2023)
Diabetes Mellitus is a group of metabolic diseases that occur due to abnormalities in insulin secretion. Diabetes is not controlled and over time causes serious damage, especially to the nerves and blood vessels. This study aims to determine the effectiveness of Active Assistive Range of Motion in reducing KGD in patients with Type II DM. This research is a quantitative study with a quasi-experimental design with one group pretest and posttest design. The population in this study was all elderly people at the Sentosa Baru Health Center, totaling 167 people. The sampling technique was purposive sampling and analysis using the T-test. The results of this study show that the Active Assistive Range of Motion is effective in reducing KGD in type II DM at the UPTD Puskesmas Sentosa Baru with the results showing that the highest KGD before the intervention was 291 mg/dL, the lowest value was 220 mg/dL, after the intervention the highest value was 204 mg. /dL, the lowest value is 190 mg/dL. the results of bivariate analysis using the T-test obtained a p-value of 0.001 or p <0.05. Expected to be information for health workers, especially the implementation of Active Assistive Range of Motion as an effort to reduce KGD in Type II DM patients.